Kandidat Galur Unggul Mutan Padi G16 Hasil Induksi Mutasi dengan Sinar Gamma: Superior Line Candidate for Rice Mutant G16 Result of Mutation Induction with Gamma Rays - Ni Wayan Sri Suliartini; I Gusti Putu Muliarta Aryana; Anak Agung Ketut Sudharmawan; I Wayan Sudika (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
The aim of this study was to obtain superior lines that had higher yields and shorter harvesting ages than their  parents. The research was conducted in Saribaye Village, Lingsar, West Lombok Districts, from February to July 2020. The study used a Single Plant Design with the treatment of the M1 G16 mutant population at irradiation doses of 200 Gy, 300 Gy, 400 Gy and 500 Gy and  parent (G16 line) as a control. Each treatment planted 200 seeds while the control was repeated three times. The variables observed included the number of productive tillers (saplings), panicle length (cm), number of filled and empty grains per panicle (grains), age of harvest (HSS), weight of 100 grains (g) and weight of filled grain per clump (g). . The value of genetic variance is calculated based on the reduction of phenotype variance with environmental variation (Mangoendidjojo, 2007). Determination of the potential for superior line candidates is done by setting the selection limit value (Xs) according to Kuswanto and Waluyo (2012). The selected genotype is a genotype that has a production value of more than Xs and an age of less than Xs. The results showed that there was an increase in genetic variance due to gamma ray irradiation treatment. A total of three mutant genotypes were successfully selected as candidates for superior strains, namely M1G16-9D3, M1G16-14D3, M1G16-27D3. The three mutant genotypes have the opportunity to be further developed into superior varieties with high yield potential and early maturity.